СЕРЦЕВА НЕДОСТАТНІСТЬ: МІСЦЕ БІОМАРКЕРІВ NT-proBNP ТА sST 2 (World Science, 2019)
Heart failure is the most common disease in recent decades. Optimizing the diagnosis and prognosis of various types of heart failure is an important task of modern medicine. The use of specific biomarkers to determine the diagnosis of heart failure, prognosis of the disease is an acute problem. To date, known biomarkers are natriuretic peptides and ST2 and its isoforms. These are highly sensitive biomarkers that allow you to personalize the risk of complications in a patient with heart failure. The article discusses both the single, single use of individual biomarkers, as well as the serial identification and combination of biomarkers to evaluate the prognosis.